Seismic Evidence of Bottom‐Up Crustal Control on Volcanism and Magma Storage Near Mount St. Helens. Issue 5 (9th March 2021) - Kiser, Eric; Levander, Alan; Schmandt, Brandon; Hansen, Steven
Abstract: The lower crust has long been recognized as a place where significant chemical evolution of magma occurs. Understanding the conditions that lead to long‐term storage in or rapid transport through these lower crustal systems has remained a challenge. In this study, active‐source seismic data are processed to image prominent reflectors in the lower crust and upper mantle near Mount St. Helens. Results show strong and weak near‐Moho reflectivity located near previously inferred regions of magma storage and high‐density bodies underlying volcanic centers, respectively. To explain these observations, we hypothesize that magmas intersecting the high‐density lower crustal bodies experience enhanced vertical buoyancy forces/transport due to the increased density contrast between melt and host rock. The reduced reflectivity near high‐density bodies is therefore a result of both decreased impedance contrasts between crust and mantle host rocks and diminished lower crust magma accumulation, which ultimately causes focusing of volcanism above these features. Key Points: Near Mount St. Helens significant variations in near Moho reflectivity are observed over lateral distances of ∼10 km Strong and weak near‐Moho reflectivity is located near inferred regions of lower crust magma storage and high‐density bodies, respectively Host rock/melt density contrasts create buoyancy that promotes volcanism and limits magma storage near the lower crust high‐density bodies